1917 Or. Gen. and Spec. Laws 804, ch. 377, § 3 - (:unkn) unknown (My University, 1917)
Provided that any person who manufactures, sells, keeps for sale, or offers for transfer a blackjack, billy, sandclub, slungshot, or metal knuckles is guilty of a misdemeanor
Keywords: TRANSFER, MANUFACTURE & POSSESSION - NON-GUN ARMS